Creative Accounting & Financial Reporting: Model Development & Empirical Testing - Tassadaq, Fizza; Malik, Qaisar Ali (International Journal of Economics and Financial Issues, 2015)
This paper empirically and critically investigates the issue of creative accounting in financial reporting. It not only analyzes the ethical responsibility of creative accounting but also focuses on other factors which influence the financial reporting like role of auditors, role of govt. regulations or international standards, impact of manipulative behaviors and impact of ethical values of an individual. Data has been collected through structured questionnaire from industrial sector. Descriptive and inferential statistics were used to generalize the results and conclude the findings. The study concluded that a company is involved in frauds or scandals because of several factors like unethical behaviors, agency problem and non professional attitude. Creative accounting is neither an illegal nor legal only the maximum use of it pushes a company in scandals. Creative accounting plays significant role in financial reporting but has been negatively correlated that means more managers involved in it may decrease the value of financial information. Govt. regulation/ international standards have positive and significant role if it is flexible in financial reporting. As auditor’s comment also plays positive and significant role in financial reporting. Ethics plays an important and positive role in financial reporting. The more ethical values mean lesser manipulative behaviors. So the manipulative behaviors only destroy the image of any company. Keywords: creative accounting; ethical values; role of auditors; government regulations; international standards; manipulative behaviors; corporate governance. JEL Classifications: M40; M41; M4